Effectiveness of Rainwater Harvesting System as Domestic use at Public University in Malaysia: A Review - INTAN SURAYA BINTI ZAHARUDDIN,; NOOR ALIZA BINTI AHMAD, (Recent Trends in Civil Engineering and Built Environment, 2022)
A rainwater harvesting system is a method or technology that collecting and storing rainwater from the rooftop for portable and non-portable use. In 2006, the government announced that it is mandatory to implement the RWH system to large buildings like schools/institutions, factories, or bungalows. Universiti Tun Hussein Onn Malaysia (UTHM), UiTM Malaysia, and Universiti Malaysia Sabah are the institutions that were implementing the RWH system. This study was conducted to review the effectiveness of the rainwater harvesting system in terms of its economic benefits at public universities in Malaysia and highlight the issue when implementing it. Data for this study were collected from secondary data sources. All the data sets were identified through secondary data source, and it will then be extracted to analyse by using a chart. The findings show that this system is effective in these three universities in terms of economic benefits where it helps reduce the water bills for UTHM, UiTM and UMS as much as RM8690.40, RM10460 and RM2309.71, respectively. This study also has shown that the issue arises when implementing this system. This system has been seen it could not cater the volume of water demand, lack of maintenance that causes the system to be full of contaminants and debris at the gutter that may block the water to enter the storage tank and also may cause the system could not function well and also lack of expertise in this fields.